Reproductive biology and spatio-temporal distribution of Stellifer rastrifer, Stellifer naso and Macrodon ancylodon (Sciaenidae) in the Caeté estuary, northern Brazil - CAMARGO-ZORRO, Mauricio (2015)
This study analyses the spatial and temporal distribution of the dominant Sciaenids in the Caeté estuary on the northern coast of Brazil. Samples were taken by otter trawls in four areas of the Caeté estuary between October 1996 and August 1997 six bimonthly. Stellifer rastrifer, Stellifer naso and Macrododon ancylodon presented the highest biomass out of eleven species of Sciaenidae caught. Minimum and mean length at first maturity were calculated and the main spawning periods determined. Changes in the spatio-temporal distribution of the three species were related to seasonal changes in estuarine salinity and spawning pulses. Larvae and juveniles of S. rastrifer, S. naso and M. ancylodon were found in the inner estuary while larger specimens were more abundant in the outer estuary with higher salinities. M. ancylodon spawned from October to February and rested from April to August whereas S. rastrifer and S. naso spawned throughout the year, though with two peaks, in October-December and June.